E-Commerce Strategy in Driving Sharing Economy in Culinary Industry - Sudiwijaya, Erwan; Ambardi, Kuskridho (Universitas Muhammadiyah Yogyakarta, 2021)
Targeting the Jakarta market, e-commerce catering had emerged to provide practical solutions for routine eating needs. The object in this study was Kulina, which was founded initially as a marketplace in 2015. The initial purpose of its establishment was to drive the sharing economy through co-creation with kitchen and distribution partners to meet the lunch needs of their customers, the employees in Jakarta. The research data was taken by interviews with Digital Marketing Manager and Customer Experience Head and Supervising Delivery. Additionally, observations were conducted on Kulina’s digital marketing communication activities on the @ Kulina.id Instagram account during September 2017-January 2018. Document searches were carried out via the internet on Instagram with the keyword #Kulina and another site containing information about Kulina based on a google search with the keyword Kulina. The study found that customer demand communicated through the website affects complementarity, development of economies of scale, and standard-setting. The information was used to open and develop a sharing economy network and business terms for Partners. Nevertheless, complementarity in Kulina was not only influenced by the meeting of suppliers and demand but also other factors such as traffic jams.